Provas cruciais da dicentricidade dos cromossômios dos hemipteros - Jor., S. de Toledo Piza (Anais da Escola Superior de Agricultura Luiz de Queiroz, 1952)
Studying the meiosis of two Hemiptera, mamely, Lybindus dichrous (Coreidae) and Euryophthalmus humilis (Pyrrhocoridae), the author has found new proofs in favor of the existence of a centromere at each end of the chromosomes of the insects belonging to that order. Following the behaviour of a pair of large autosomes of Lybindus, he was able to verify that in the first division of the spermatocytes, the tetrad they form divides transversely by the middle, giving rise to two V-shaped anaphase chromosomes that go to the poles with the vertex pointing forwardly. From the end of the first division till the metaphase of the second one, the centromeres occupying the vertex of the V go apart from one another, making the chiasmata existing there slip to the opposite extremities, what changes the V into an X. When the chiasmata reach the acentric ends, the X is again converted into a V. The V of the secondary metaphase, therefore, differs from the V of the primary anaphase, in being inverted that is, in having the centromeres in the extremity of its arms, and no longer in the vertex as in the latter. The opening out of the chromosomes starting at the centric extremities in order to recuperate the dumbbell shape they show in the secondary anaphase, just in the manner postulated by PIZA, is thus demonstrated. In Euryophthalmus humilis it was verified once more, that the heterochromosome, in the secondary spermatocytes, orients parallelly to the spindle axis, accompanying with its ends the anaphase plates as they move to the poles. The author is in disagreement with NORONHA-WAGNER & DUARTE DE CASTRO's interpretation of the behaviour of the chromosomes in meiosis of Luzula nemorosa.